2023
DOI: 10.1186/s12876-023-02720-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel inflammatory marker for extensive ulcerative colitis; Endocan

Abstract: Background & aims Ulcerative colitis (UC) is an inflammatory bowel disease characterized by mucosal inflammation. Endocan, a proteoglycan secreted by endothelial cells in response to inflammatory cytokines, has been reported to be overexpressed in inflammatory conditions. In this study, we aimed to evaluate the utility of endocan level in determining the extent and severity of disease in patients with ulcerative colitis and to determine whether it can be a candidate marker for noninvasive e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In a study by Albayrak et al, endocan levels, secreted by endothelial cells in response to inflammatory cytokines, were shown to be useful in determining the prevalence of ulcerative colitis characterized by mucosal inflammation and could be beneficial in treatment planning. [23,24] Elevated levels of endocan, similar to SAL-β, were found in both patients with AP and severe ulcerative colitis, aligned with the design of our study. Ultimately, biomarkers identified as elevated in severe pancreatitis can be used for prognosis monitoring and assist clinicians.…”
Section: Discussionsupporting
confidence: 85%
“…In a study by Albayrak et al, endocan levels, secreted by endothelial cells in response to inflammatory cytokines, were shown to be useful in determining the prevalence of ulcerative colitis characterized by mucosal inflammation and could be beneficial in treatment planning. [23,24] Elevated levels of endocan, similar to SAL-β, were found in both patients with AP and severe ulcerative colitis, aligned with the design of our study. Ultimately, biomarkers identified as elevated in severe pancreatitis can be used for prognosis monitoring and assist clinicians.…”
Section: Discussionsupporting
confidence: 85%
“…Another important finding in this report is that the young adult colchicine users were associated with the lower aHR of colorectal cancer among the IMIDs [ 21 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patients who used colchicine between 2000 and 2012 were defined as colchicine users among patients with IMIDs ( N = 23,612) [ 6 8 , 20 , 21 ]. The colchicine users need to fulfill criteria as below: in Lin et al’s study, the nude mice experiment showed that colchicine-treated mice after 14 days of treatment had lower increased tumor volume ratios and tumor growth rates than the control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation